PENGARUH MODEL PEMBELAJARAN CORE TERHADAP KEMAMPUAN KONEKSI MATEMATIS DAN MOTIVASI BELAJAR SISWA - Krisna Triyanti; Jumroh Jumroh; Allen Marga Retta (Universitas Muhammadiyah Bengkulu, 2019)
The Connecting, Organizing, Reflecting, Extending (CORE) learning model is a learning model that has the design of constructing students' abilities by connecting and organizing knowledge, then rethinking the concept being studied. The purpose of this study is to find out whether or not the influence of the learning model Connecting, Organizing, Reflecting, Extending the ability of mathematical connections, and to find out the motivation of students learning at SMK YP Gajah Mada Palembang. The population in this study were all students of class XI, amounting to 420. The sample taken in this study was class XI TITL 4, totaling 30 students as an experimental class taught using the CORE learning model and class XI TPM totaling 27 people as a control class taught using conventional learning. The design of the experimental method used is Posttest-Only Control Design. Data collection techniques using test and non-test techniques. Data were analyzed using an independent sample t test, with a significance level of 5%. The results of this study are that there is a significant influence between the learning models of Connecting, Organizing, Reflecting, Extending (CORE) on the ability of mathematical connections and motivation to learn students of SMK YP Gajah Mada Palembang. Â Keywords: CORE, Mathematical connection, learning motivation